Motional heterogeneities in siloxane/poly(ethylene glycol) ormolyte nanocomposites studied by C-13 solid-state exchange NMR - deAzevedo, E. R.; Reichert, D.; Vidoto, ELG; Dahmouche, K.; Judeinstein, P.; Bonagamba, T. J. (Amer Chemical Soc, 2003)
C-13 exchange solid-state NMR methods were used to study two families of siloxane/poly-(ethylene glycol) hybrid materials: Types I and II, where the polymer chains interact with the inorganic phase through physical (hydrogen bonds or van der Waals forces) or chemical (covalent bonds) interactions, respectively. These methods were employed to analyze the effects of the interactions between the organic and inorganic phases on the polymer dynamics in the milliseconds to seconds time scale, which occurs at temperatures below the motional narrowing of the NMR line width and around the polymer glass transition. Motional heterogeneities associated with these interactions and evidence of both small and large amplitude motions were directly observed for both types of hybrids. The results revealed that the hindrance to the slow molecular motions of the polymer chains due to the siloxane structures depends on the chain length and the nature of the interaction between the organic and inorganic phases.